Modified ZnO for Efficient Photo-Catalysis by Silver/Graphite oxide Nanoparticles - Firas H. Abdulrazzak (Journal of Global Pharma Technology, 2016)
ZnO was modified with ternary composites Ag:ZnO/GOto enhance the interaction/reaction activities by simple evaporation/ photo-deposition of Graphite oxide and Silver respectively. The ternary composites were characterized by analysis the structure or morphology with X-ray diffraction, UV-visible diffraction to find band gap and surface area SBET. The process include change in sequence of preparations which tested by removing Eosin yellow by adsorption and photocatalytic degradation. The results shows that ZnO after modifications was more active then pristine phase and Ag :(ZnO/GO) was more activities then (Ag:ZnO)/GO in photo-reaction but less abilities in adsorption.Keywords:  Eosin Yellow, Ternary composites, Ag: ZnO/GO, Degradation.